1998
DOI: 10.1159/000026184
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Multifocal Leukoencephalopathy in the United States, 1979–1994: Increased Mortality Associated with HIV Infection

Abstract: To examine trends in progressive multifocal leukoencephalopathy (PML) mortality in the United States, we analyzed PML death rates and deaths for 1979 through 1994, using US multiple cause-of-death data. During the 16-year study period 3,894 PML deaths were reported. The age-adjusted death rate increased more than 20-fold, from less than 0.2 per million persons before 1984 to 3.3 per million persons in 1994. The increase was attributable to infection with human immunodeficiency virus (HIV) which was recorded on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…In the general population, PML is estimated to occur at 1 case per 200 000 persons. 67 Among HIV-infected populations, incidence rates decreased from 3.3 cases per 1000 person-years at risk in 1995 to 1996 to 1.3 cases per 1000 person-years at risk in 2000 to 2006, after the introduction of highly active antiretroviral therapy. 46 Among persons with multiple sclerosis or Crohn disease, the estimated incidence of natalizumab-associated PML is 1 PML case per 1000 natalizumab-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, PML is estimated to occur at 1 case per 200 000 persons. 67 Among HIV-infected populations, incidence rates decreased from 3.3 cases per 1000 person-years at risk in 1995 to 1996 to 1.3 cases per 1000 person-years at risk in 2000 to 2006, after the introduction of highly active antiretroviral therapy. 46 Among persons with multiple sclerosis or Crohn disease, the estimated incidence of natalizumab-associated PML is 1 PML case per 1000 natalizumab-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of Progressive Multifocal Leukoencephalopathy (PML) in the United States increased in parallel with the AIDS epidemic from 1 in 10 million to over 1 in 500,000 between 1979 and 1992 (Holman et al, 1998). The introduction of highly active antiretroviral therapies (HAART) has increased the mean survival time of AIDS patients with PML from 2 months to one year but has had no effect at reducing the overall incidence of PML in the HIV infected population (Koralnik, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In immunosuppressed patients, JCV causes a fatal demyelinating disease known as progressive multifocal leukoencephalopathy (PML). PML occurs predominately in immunosuppressed patients with the majority of cases occurring in the setting of HIV infection (Holman et al, 1998). Recently, PML has also been reported in patients being treated with Natalizumab, a drug designed to inhibit leukocyte trafficking into inflamed tissue (Kleinschmidt-DeMasters and Tyler, 2005;Langer-Gould et al, 2005;Van Assche et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…14 That same year, a study of vital statistics on patients with AIDS reported to the Centers for Disease Control revealed that 0.72% of death certificates listed PML among the diagnoses. 15 A study of hospitalized patients at a large, universityaffiliated, public health trust hospital in Miami, Florida, revealed that nearly 4% of all hospitalized AIDS patients had PML. 16 An autopsy series of nearly 1,000 patients reported in 1991 similarly showed that 4% of HIV-infected individuals died with neuropathologically confirmed PML.…”
Section: Aids and Pmlmentioning
confidence: 99%